CELL CONTACTS IN THE MOUSE MAMMARY GLAND : I. Normal Gland in Postnatal Development and the Secretory Cycle - Pitelka, Dorothy R. (The Rockefeller University Press, 1973)
The nature and distribution of cell contacts have been examined in thin sections and freeze-fracture replicas of mammary gland samples from female C3H/Crgl mice at stages from birth through pregnancy, lactation, and postweaning involution. Epithelial cells of major mammary ducts at all stages examined are linked at their luminal borders by junctional complexes consisting of tight junctions, variable intermediate junctions, occasional small gap junctions, and one or more series of desmosomes. Scattered desmosomes and gap junctions link ductal epithelial and myoepithelial cells in all combinations; hemidesmosomes attach myoepithelial cells to the basal lamina. Freeze-fracture replicas confirm the erratic distribution of gap junctions and reveal a loose, irregular network of ridges comprising the continuous tight-junctional belts. Alveoli develop early in gestation and initially resemble ducts. Later, as alveoli and small ducts become actively secretory, they lose all desmosomes and most intermediate junctions, whereas tight and gap junctions persist, The tight-junctional network becomes compact and orderly, its undulating ridges oriented predominantly parallel to the luminal surface. It is suggested that these changes in junctional morphology, occurring in secretory cells around parturition, may be related to the greatly enhanced rate of movement of milk precursors and products through the lactating epithelium, or to the profound and recurrent changes in shape of secretory cells that occur in relation to myoepithelial cell contraction, or to both.